Spontaneous catanionic vesicles formed by the interaction between an anionic β-cyclodextrins derivative and a cationic surfactant - Silva, Oscar Fernando (2018)
The present work shows the synthesis of a new type of catanionic surfactant, ModCD14-BHD, which involves an anionic amphiphilic cyclodextrin and the cationic benzyl-n-hexadecyldimethylammonium (BHD). It is obtained from the simple association of the cationic surfactant benzyl-n-hexadecyldimethylammonium chloride (BHDC) and β-cyclodextrin (β-CD) monosubstituted with an alkenyl succinate group (Mod-β-CD14). ModCD14-BHD form unilamellar vesicles spontaneously in water, while the individual components (BHDC and Mod-β-CD14) do not. The vesicles were character-ized by dynamic light scattering (DLS), transmission electron microscopy (TEM), scanning electron microscopy (SEM) and 1H NMR techniques. We suggest that the formation of an inclusion complex between some of the cyclodextrins units and the long hydrocarbon moiety of the cationic surfactant play a crucial role in the vesicles formation. Besides, some or the cavities are available to interact with an external guest. We think that the new surfactant molecule has properties that may lead to important applications in biomedical and pharmaceutical sciences.